2016
DOI: 10.3177/jnsv.62.295
|View full text |Cite
|
Sign up to set email alerts
|

Rice Bran Extract Reduces the Risk of Atherosclerosis in Post-Menopausal Vietnamese Women

Abstract: SummaryWe investigated whether pre-germinated brown rice bran extract containing acylated steryl glucosides (PSG) reduces the risk of atherosclerosis in post-menopausal Vietnamese women. A total of 60 post-menopausal Vietnamese women (45-65 y old) with high LDL cholesterol levels (over 140 mg/dL) were randomly divided into PSG (n530) and placebo (n530) groups. The subjects in the PSG group were assigned a daily intake of 6 capsules containing 50 mg PSG, and the subjects in the placebo group were assigned a dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Ferulic acid-enriched rice bran oil consumption can decrease LDL-C levels in hyperlipidemic patients [ 12 ]. Furthermore, a recent clinical trial showed that supplementation with rice bran extract can reduce LDL-C and TNF-α levels in post-menopausal women with high LDL-C levels [ 38 ]. Previous study reported that rice bran consists of ferulic acid about 9000 mg/kg [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ferulic acid-enriched rice bran oil consumption can decrease LDL-C levels in hyperlipidemic patients [ 12 ]. Furthermore, a recent clinical trial showed that supplementation with rice bran extract can reduce LDL-C and TNF-α levels in post-menopausal women with high LDL-C levels [ 38 ]. Previous study reported that rice bran consists of ferulic acid about 9000 mg/kg [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The participants in the intervention group received 50 mg of acylated steryl glucosides (PSG) brown rice bran extract (6 capsules), while the placebo group received six capsules of corn oil. The results showed a significant reduction in LDL cholesterol in the intervention group compared to the placebo group (from 163 ± 25.3 mg/dL vs. 135.9 ± 26.8mg/dL), and decreased TNF α, inflammatory marker (from 6.6 ± 5.5% to 4.72 ± 6 respectively [71]. Another long-term one-year pre-post intervention trial in 66 participants with hyperlipidemia found that following a plant-based diet for one year led to a significant reduction in blood pressure and LDL cholesterol that was maintained at the one-year follow-up [72].…”
Section: Fiber Blood Cholesterol and Atherosclerosismentioning
confidence: 99%
“…Bioactive compounds in RB are believed to target pathways involving oxidative stress, thrombogenesis, and vascular inflammation via their antioxidant activity. The presence of acylated steryl glucosides [27], flavonoids [28], ferulic acid [29], policosanol [30], resveratrol [31] and plasma metabolites [32] from RB have been demonstrated to exhibit antioxidant, anti-inflammatory and free radical scavenging properties consequently instrumental in preventing or delaying the occurrence of CVD.…”
Section: Rice Bran Derived Bioactive Compounds and Biomarkers Of Cmentioning
confidence: 99%
“…Moreover, levels of diet-derived amino acids, bioactive chemicals (particularly salicylate) and cofactors/vitamins (e.g., pyridoxal, an active form of vitamin B6) increased compared to the control after RB consumption [32]. In another study, pre-germinated RB extract containing acylated steryl glucosides (PSG) (6 capsules/day containing 50 mg of PSG) was found to significantly reduce serum low-density lipoprotein (LDL) and TNF-α levels [27]. These results demonstrate that consumption of RB and navy bean can impact blood lipid metabolism with implications for reducing CVD risk in children.…”
Section: Rice Bran Derived Bioactive Compounds and Biomarkers Of Cmentioning
confidence: 99%